Modelling the effectiveness of an isolation strategy for managing mpox outbreaks with variable infectiousness profiles - Jeong, Yong Dam; Hart, William S.; Thompson, Robin N.; Ishikane, Masahiro; Nishiyama, Takara; Park, Hyeongki; Iwamoto, Noriko; Sakurai, Ayana; Suzuki, Michiyo; Aihara, Kazuyuki; Watashi, Koichi; Op de Coul, Eline; et al. (Nature communications, 2024)
The global outbreak of mpox in 2022 and subsequent sporadic outbreaks in 2023 highlighted the importance of nonpharmaceutical interventions such as case isolation. Individual variations in viral shedding dynamics may lead to either premature ending of isolation for infectious individuals, or unnecessarily prolonged isolation for those who are no longer infectious. Here, we developed a modeling framework to characterize heterogeneous mpox infectiousness profiles – specifically, when infected individuals cease to be infectious – based on viral load data. We examined the potential effectiveness of three different isolation rules: a symptom-based rule (the current guideline in many countries) and rules permitting individuals to stop isolating after either a fixed duration or following tests that indicate that they are no longer likely to be infectious. Our analysis suggests that the duration of viral shedding ranges from 23 to 50 days between individuals. The risk of infected individuals ending isolation too early was estimated to be 8.8% (95% CI: 6.7–10.5) after symptom clearance and 5.4% (95% CI: 4.1–6.7) after 3 weeks of isolation. While these results suggest that the current standard practice for ending isolation is effective, we found that unnecessary isolation following the infectious period could be reduced by adopting a testing-based rule. Current guidelines recommend that individuals exposed to mpox should isolate for three weeks, based on the average estimated incubation period. Here, the authors use a quantitative model to characterise mpox infectiousness profiles and quantify the impacts of different isolation rules.